KOORDINASI ANTARA PEMERINTAH DESA DAN DINAS PERTANIAN DALAM PEMBERDAYAAN KELOMPOK TANI (Studi Kasus: Desa Fajar Jaya, Kecamatan Lengkiti, Kabupaten Ogan Komering Ulu) - Rio Nusantara; Marratu Fahri; Eva Susanti (Jurnal Riset Multidisiplin Edukasi, 2026)
Fajar Jaya Village is a rural area where the majority of the population works as farmers; however, not all farmers are involved in farmer groups. Out of 652 farmers, only 286 are registered as active members of farmer groups. This condition indicates that empowerment programs have not reached the entire farming community. The main issue identified is the suboptimal coordination between the Village Government and the Department of Agriculture, characterized by a lack of data synchronization, the absence of regular communication forums, unclear division of tasks, and weak joint evaluation mechanisms. These problems serve as the primary basis for conducting research on coordination patterns in empowering farmer groups in Fajar Jaya Village.This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation. The theoretical framework is based on Hasibuan’s concept of coordination, which focuses on four indicators: cooperation, communication, division of labor, and discipline. The study was conducted from May 20 to June 24, 2025, in Fajar Jaya Village and the Department of Agriculture of Ogan Komering Ulu Regency. The findings reveal that coordination remains administrative, lacks participatory elements, and is not yet integrated into the village development planning process. Based on these findings, it is concluded that coordination between the two parties has not been optimal. The researcher recommends the establishment of a formal coordination forum, increased involvement of the village in planning, clearer division of responsibilities, and strengthened communication and documentation to ensure that empowerment programs become more effective and sustainable.